Do rates matter? Validation of insect frass fertilizer rates in a vegetable intensified push-pull technology for optimal sustainable production - Kimuli, Priscilla Mwikali; Beesigamukama, Dennis; Wambua, Judy; Sokame, Bonoukpoe Mawuko; Tanga, Chrysantus Mbi; Chidawanyika, Frank; Subramanian, Sevgan; Mutyambai, Daniel Munyao (Frontiers in Agronomy, 2025)
Push–pull system intensification with vegetables (VIPPT) has contributed significantly in maintaining good control of lepidopteran pests and parasitic weeds with additional food and nutritional security benefits. However, the impact of integration of different rates of black soldier fly frass fertilizer (BSFFF) in the VIPPT to enhance productivity, has not been explored. This study investigated the effects of different BSFFF application rates on growth performance, pest infestation severity, diversity of natural enemies and yield of kale (Brassica oleracea L. var. acephala) grown under VIPPT in two agroecological zones. Plants were grown in soils amended with five different levels of BSFFF (0, 50, 100, 150 and 200) kg N ha-1), blends with inorganic fertilizers, (Di-ammonium phosphate (DAP) and Nitrogen, Phosphorous and Potassium (NPK)), and unfertilized soil (control). Across the two sites, plants treated with 200 BSFFF exhibited faster growth and higher yield (by 7% and 82%) compared to 150BSFFF and 0BSFFF, respectively. Similarly, aphid infestation was lower in the 200BSFFF treatment (by 64% and 1%) compared to inorganic fertilizer and 0BSFFF. Additionally, natural enemies such as Coleoptera (35% and 97%), Hemiptera (17% and 97%) and Diptera (100% and 44%) were more abundant in 200BSFFF than 0BSFFF and inorganic fertilizer treatments, respectively. Our findings demonstrate that integration of VIPPT and BSFFF at an application rate of 200 Kg N ha-1 BSFFF significantly improves growth and yield of kales while reducing the severity of pest infestation and conserves natural enemies of key cruciferous pests. The synergistic effects of these technologies hold great promise towards sustainable vegetable production, environmental and biodiversity conservation.